ANALISIS PERBANDINGAN EFISIENSI ALAT PANCANG DIESEL HAMMER DAN DROP HAMMER PADA PEKERJAAN PONDASI TIANG PANCANG DI LAHAN BASAH - Candra Yuliana Candra; Retna Hapsari K; Eva Puspita Sari (Jurnal Infrastruktur, 2021)
The pile driving method requires the management of heavy equipment such as pile drivers as the main equipment for the construction of pile foundations. Pile driver productivity is very influential in terms of time and cost during implementation. Therefore, it is necessary to study the productivity of the pile driver by comparing the Diesel Hammer and Drop Hammer in a project. The driving work with Diesel Hammer tools produces a productivity of 17.98 m/hour, the total duration of driving is 21 points for 49 hours with equipment rental of Rp. 15.240.000,-. Meanwhile, with the Drop Hammer the productivity is 11.71 m/hour, the duration is 77 hours, the total equipment rental is Rp. 14,940,000,-. In terms of time and cost efficiency with a certain depth, there are significant time and cost differences between the two tools. Both pile drivers have advantages and disadvantages, but in terms of time and cost efficiency. Based on the time aspect, the Diesel Hammer is more efficient than the Drop Hammer, but it is necessary to consider the cost aspect.